Development of In-Vivo Biofuel Cell for implantable medical devices - Mohd. Salleh, Hamzah; Mohd Yusoff, Nur Syaheera; Othman, Raihan; Abd Wahab, Mohd Firdaus (IIUM Press, 2011)
The electrochemical aCtivIty of human leukocytes (white blood cells and platelets) was investigated by measuring the current output and open circuit potential produced from a biofuel cell (BFC). White blood cells and platelets were isolated from whole human blood, suspended in phosphate buffered saline solution and introduced to the anode compartment of the biofuel cell. Red blood cells were isolated and introduced to the cathode. Measurements of current and open circuit potential were conducted once the BFC was assembled. The results of this study indicate the possibility of functionalizing an in-vivo biofuel cell utilizing human blood as the energy source.